Accounting for investment risk in educational decisions: New evidence for lifetime returns in Germany - Anne Zühlke; Philipp Kugler; Armin Hackenberger; Tobias Brändle (Institut für Angewandte Wirtschaftsforschung (IAW), 2020)
We analyse the economic returns in lifetime labour income of different educational paths in Germany, especially the difference between university studies and vocational training. New data allows us to calculate cumulative labour earnings at different ages and to compare not only the highest educational degree, but also which educational paths have been taken, as well as the educational background of individuals. We find that lifetime labour income is higher for individuals with a university degree, but only late in life. When considering the failure risk of educational degrees and the possibility of educational upgrading, we find that individuals who start with a vocational training after their highest school degree do not earn less than individuals who start with university studies, once we control for covariates such as socio-demographics and educational background.
Keywords: I21; I26; J17; J24; 330; returns to education; lifetime income; educational upgrading; college dropout; apprenticeship training; NEPS‐ SC6‐ ADIAB